Just Who Was Wearing the Trousers in Victorian Britain? Violent Wives and Violent Women - Anne-Marie Kilday (Cahiers Victoriens et Edouardiens)
Intra-marital violence is a subject often examined by sociologists, psychologists and historians alike, albeit from a very traditional perspective. Certainly, the image of the ‘battered wife’ is a common one when discussions of domestic aggression arise or literature on the subject is produced. What though, of the ‘battered husband’? Evidence from nineteenth century Scottish and English church and court records suggest that abusive behaviour by wives against their husbands was not uncommon, and indeed, more often than not, the violence meted out by these women was in a physical sense, more ‘damaging’ than that inflicted by their male counterparts.The intention of this paper therefore, is to examine—through a balanced gendered perspective—the ways in which domestic violence was carried out, the apparent reasons for this behaviour and the consequences of this type of aggressive activity for both offender and victim, regardless of sex.In doing this, it is hoped that the paper will shed new light on a traditionally one-sided argument.